Determinants of Cybersecurity Behavior among Social Media Users: The Moderating Role of Self-Efficacy in the Relationship between Cybersecurity Knowledge and Social Media Use Intensity - Saputra, Hadi Kurnia; Refdinal, Refdinal; Abdullah, Rijal; Mardizal, Jonni; Ambiyar, Ambiyar; Fadhilah, Fadhilah (Universitas Negeri Padang, 2025)
Social media has become an integral part of daily life, but its intensive use also increases users’ exposure to various cybersecurity threats, making it important to understand the determinants of cybersecurity behavior. This study examines the effects of cybersecurity knowledge and social media usage intensity on cybersecurity behavior, as well as the role of cybersecurity self-efficacy as both a direct predictor and a moderating variable. A quantitative approach was employed using a survey of 115 university students who actively use social media, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that cybersecurity knowledge has a positive and significant effect on cybersecurity behavior (β = 0.309, t = 3.383, p < 0.01), while cybersecurity self-efficacy emerges as the strongest predictor of cybersecurity behavior (β = 0.479, t = 4.725, p < 0.001). In contrast, social media usage intensity does not show a significant effect on cybersecurity behavior (β = 0.003, t = 0.032, p > 0.05). Furthermore, moderation analysis reveals that cybersecurity self-efficacy does not moderate the relationships between cybersecurity knowledge or social media usage intensity and cybersecurity behavior. The structural model explains 58.3% of the variance in cybersecurity behavior (R² = 0.583). These findings suggest that cybersecurity behavior among social media users is more strongly driven by cognitive and psychological factors than by usage intensity alone. Practically, effective cybersecurity interventions should prioritize strengthening users’ cybersecurity knowledge and self-efficacy rather than merely restricting social media use.Keywords— Cybersecurity behavior; Cybersecurity knowledge; Self-efficacy; Social media usage intensity; SEM-PLS